ANALISIS PENYEBAB KESULITAN BELAJAR KANJI MAHASISWA PRODI PENDIDIKAN BAHASA JEPANG UNIVERSITAS NEGERI PADANG - fikry octha feranda; Damai Yani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2022)
“Analysis of the causes of difficulty in learning kanji for students of Japanese language education study program”. Thesis. Japanese Language Education Study Program, Department of English Language and Literature, Faculty of Language and Arts, Padang State University. This study aims to find out what are the causes of students' difficulties in learning kanji in the Japanese Language Education Study Program, Padang State University. This type of research is descriptive quantitative. The population in this study amounted to 60 students. The sample in this study was the entire population using total sampling technique. Data collection techniques using a questionnaire with a Likert scale. The data analysis technique used is descriptive with percentages. The results of this study are the average of the questionnaires causing difficulty in learning kanji Japanese Language Education Study Program, Padang State University, which obtained results of 70.65% based on the category classified as "High". Which has a low impact meaning on causing kanji learning difficulties. Both in terms of external and internal.